Ochikubo Monogatari or The Tale of the Lady Ochikubo : a Tenth Century Japanese Novel. - Whitehouse, Wilfrid (Routledge Library Editions., 2010)
This is a selection of the best plays of Chikamatsu, one of the greatest Japanese dramatists. Master of the marionette and popular dramas, he had, until the publication of this book, remained unknown to western readers owing to the difficulty of translating the work into English.